On-Label or Off-Label? Overcoming Regulatory and Financial Barriers to Bring Repurposed Medicines to Cancer Patients - Verbaanderd, Ciska; Rooman, Ilse; Meheus, Lydie; Huys, Isabelle (Frontiers in Pharmacology, 2020)
Repurposing of medicines has gained a lot of interest from the research community in recent years as it could offer safe, timely and affordable new treatment options for cancer patients with high unmet needs. Increasingly, questions arise on how new uses will be translated into clinical practice, especially in case of marketed medicinal products that are out of basic patent or regulatory protection. The aim of this study was to portray the regulatory framework relevant for making repurposed medicines available to cancer patients in Europe and propose specific policy recommendations to address the current regulatory and financial barriers. We outlined two routes relevant to the clinical adoption of a repurposed medicine. First, a new indication can be approved, and thus brought on-label, via the marketing authorisation procedures established in European and national legislation. Such procedures initiate a detailed and independent assessment of the quality and the benefit-risk balance of a medicinal product in a specific indication, benefiting both prescribers and patients as it reassures them that the scientific evidence is robust. However, the process of marketing authorisation for new therapeutic indications entails a high administrative burden and significant costs while the return-on-investment for the pharmaceutical industry is expected to be low or absent for medicines that are out of basic patent and regulatory protection. Moreover, most of the repurposing research is conducted by independent or academic researchers who do not have the expertise or resources to get involved in regulatory procedures. A second option is to prescribe a medicine off-label for the new indication, which is managed at the national level in Europe. While off-label use could provide timely access to treatments for patients with urgent medical needs, it also entails important safety, liability and financial risks for patients, physicians and society at large. In view of that, we recommend finding solutions to facilitate bringing new uses on-label, for example by developing a collaborative framework between not-for-profit and academic organizations, pharmaceutical industry, health technology assessment bodies, payers and regulators.